Application of femtosecond Ti-Sa lasers for measuring of amplitude-frequency characteristics of wide-band photodevices - Vasilyev, A.V.; Zajtsev, V.P.; Leshchenko, V.P.; Povrozin, A.I. (Вопросы атомной науки и техники, 2013)
A possibility of an application of the femtosecond Ti-Sa lasers for a measuring of the amplitude-frequency characteristics (AFC) of the wide-band photodevices is considered. The results of the measuring of the AFC in a frequency range 1.5 GHz for a high-speed photodiode S5972 of the firm “Hamamatsu” are presented.